Moja mama je došla s jednin vapor: italianismos na fala dos imigrantes dálmatas na Argentina - Bilic, Josip Bruno (2025)
The aim of this study is to examine the Italian loanwords incorporated into the speech of Dalmatian migrants in Argentina. In Dalmatia, a region in southern Croatia, the Italian influence—still present today—stems from factors of prestige and is particularly evident in the local lexicon. Among the languages spoken by migrants who arrived during various waves of migration, there is a notable presence of Italian loanwords. Drawing on speech recordings of Dalmatian migrants in Argentina and a corpus of semi-structured interviews, this study will explore the formal characteristics of Italianisms across different structural levels, as well as their communicative functions and roles in the construction of identity. This work is part of a larger research project on Croatian speech in Argentina (Bilic, 2022) and contributes to the growing interest in cataloging Italianisms (Heinz, 2017) to examine the unique features of each receiving language and deepen our understanding of linguistic contact phenomena.